2021
DOI: 10.1007/s00239-021-10012-6
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Molecular Evolution of Mammalian Homeobox Genes: Duplication, Loss, Divergence and Gene Conversion Sculpt PRD Class Repertoires

Abstract: The majority of homeobox genes are highly conserved across animals, but the eutherian-specific ETCHbox genes, embryonically expressed and highly divergent duplicates of CRX, are a notable exception. Here we compare the ETCHbox genes of 34 mammalian species, uncovering dynamic patterns of gene loss and tandem duplication, including the presence of a large tandem array of LEUTX loci in the genome of the European rabbit (Oryctolagus cuniculus). Despite extensive gene gain and loss, all sampled species possess at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(36 citation statements)
references
References 171 publications
(263 reference statements)
3
33
0
Order By: Relevance
“…Second, we constructed expression plasmids carrying bovine homeobox genes ARGFX or LEUTX driven by a constitutive promoter, each connected by a peptide linker to a C-terminal 3xFLAG tag to facilitate downstream analysis. We also constructed an expression plasmid carrying a mutant allele of ARGFX identified in the ARS-UCD1.2 reference genome ( Lewin et al 2021 ). This allele has a 13 base pair (bp) deletion before the homeodomain resulting in a frameshift and truncated predicted protein.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Second, we constructed expression plasmids carrying bovine homeobox genes ARGFX or LEUTX driven by a constitutive promoter, each connected by a peptide linker to a C-terminal 3xFLAG tag to facilitate downstream analysis. We also constructed an expression plasmid carrying a mutant allele of ARGFX identified in the ARS-UCD1.2 reference genome ( Lewin et al 2021 ). This allele has a 13 base pair (bp) deletion before the homeodomain resulting in a frameshift and truncated predicted protein.…”
Section: Resultsmentioning
confidence: 99%
“…We previously identified a 13 bp deletion in the coding region of the ARGFX gene of the B. taurus reference genome ARS-UCD1.2 and showed that the indel is polymorphic, as several RNA-seq datasets exhibit the wild type (WT) allele ( Lewin et al 2021 ). Here, we investigate the frequency of the deletion allele and its effect on protein function.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations